Inference in economic experiments - Norbert Hirschauer; Sven Grüner; Oliver Mußhoff; Claudia Becker (Kiel Institute for the World Economy (IfW), 2019)
Replication crisis and debates about p-values have raised doubts about what we can statistically infer from research findings, both in experimental and observational studies. With a view to the present debate on inferential errors, this paper systematizes and discusses experimental designs with regard to the inferences that can and - perhaps more important - that cannot be made from particular designs.
Keywords: B41; C18; C90; 330; economic experiments; ceteris paribus; confounders; control; inference; Internal/external validity; randomization; random sampling; superpopulation